问题 解答题
(1)-42÷(-2)3+1÷(-
1
2
)3

(2)(-125
5
7
)÷(-5)-2.5÷
5
8
×(-
1
4
)

(3)(8xy-x2+y2)-3(-x2+y2+5xy)
(4)x-
1-x
3
=
x+2
6
-1

(5)
0.2x+1
0.3
-
0.02x+0.1
0.07
=1
答案

(1)-42÷(-2)3+1÷(-

1
2
)3

=-16÷(-8)+1÷(-

1
8

=2-8

=-6;

(2)(-125

5
7
)÷(-5)-2.5÷
5
8
×(-
1
4
)

=25

1
7
-
5
2
×
8
5
×(-
1
4

=25

1
7
+1

=26

1
7

(3)(8xy-x2+y2)-3(-x2+y2+5xy)

=8xy-x2+y2+3x2-3y2-15xy

=2x2-2y2-7xy;

(4)x-

1-x
3
=
x+2
6
-1,

6x-2(1-x)=x+2-6,

6x-2+2x=x+2-6,

7x=-2,

x=-

2
7

(5)

0.2x+1
0.3
-
0.02x+0.1
0.07
=1,

2x+10
3
+
2x+10
7
=1,

7(2x+10)+3(2x+10)=21,

14x+70+6x+30=21,

20x=-79,

x=-3.95.

单项选择题
多项选择题